CRANIOCEREBRAL TRAUMA: NURSING DIAGNOSIS FOR VICTIMS ASSISTANCE ON INTESIVE CARE UNITY. - Rita Edna da Silveira; Maria Célia de Freitas; Daniela de Souza Feitoza (Universidade Federal de Goias, 2004)
The enfermagem process makes possible a care individualized the customers, characterizing anautonomous work and quality attendance. It was aimed at to Identify diagnoses of Enfermagem in patienttraumatismos victims cranium-encefálico (TCE) and to elaborate a model of implantation of cares, through thetaxonomia NANDA, being used the reasoning of Risner. He/she/you took place descriptive-exploratory study,retrospective to the patients interned in the year 2002, type case study, reference hospital in traumatologia, inFortaleza-Ce. It was collected the data in the books of registration of UTIs I II, III, IV and, data processing Center, themonths of January to March of 2003. It was counted 143 (100%) patient interned. They were stood out TCE with 57(40%) of the cases, followed by the politraumatismos with TCE with 30 (21%) and traumatismos raqui-medular 11(7,5%). He/she/you becomes important to implement the enfermagem process that allows to plan the attendance, tooptimize time and to guarantee the quality of the care.